Patient-derived organoids reveal marked heterogeneity in chemosensitivity profiles of colorectal cancer and a potential association with HER2 status - Liu, Jian; Li, Dan; Li, Jing; Fu, Wenlan; Jia, Qiang; Bai, Yang; Huang, Axiu; Chen, Fang (Frontiers in Pharmacology, 2025)
This study aimed to evaluate the sensitivity and heterogeneity of standard first-line chemotherapy regimens for colorectal cancer (CRC) using patient-derived tumor organoids (PDTOs). Drug sensitivity testing in 15 CRC PDTOs revealed varying proportions of samples classified as sensitive (inhibition rate >50%) across different regimens: FOLFIRI (60%), FOLFOX (40%), CAPEOX (26.7%), and 5-Fluorouracil (26.7%). Furthermore, exploratory analysis indicated that for FOLFIRI and FOLFOX regimens, HER2(1+) status was significantly associated with lower inhibition grades compared to HER2(0) status (P < 0.05), implying a potential impact on the level of drug response. These findings demonstrate significant heterogeneity in the response of CRC PDTOs to first-line chemotherapies. Furthermore, at the organoid level, a low HER2 expression status may be associated with the heterogeneity of responses observed with specific drug regimens.